THE ROLE OF GERIATRIC NURSES IN MANAGING POLYPHARMACY - Fatimah Ali Alqassi,⁠ Salha Mohammed Najeay, ⁠Hamsaa Alhumaidi Alqahtani,⁠ Huda Saeed Alshahrani,⁠ Kholoud Saleem Aljehani,⁠ Ashwaq Ruwayshid Alanazi,⁠ Najla Abdullah Barzig, Badar Majid Mubark Aldossari,; Muneerah Mohammad Alotibi, Sanaa Nasser Abuallah, Amal Mohammad Saeed Aldossari,⁠ Hatim Mohammed, Shuwayfin Alotaibi, Zainab Ateeq Kaleefah Baleis, (Chelonian Research Foundation, 2022)
The phenomenon of polypharmacy is becoming a growing health problem among the elderly population, leading to several health hazards. Nurses play a crucial role in facilitating medication management and enhancing drug safety in various healthcare environments. The objective of this research is to conduct a meta-synthesis of qualitative studies that examine the viewpoints and encounters of nurses in the provision of care for older individuals who have polypharmacy. A search was conducted in electronic databases such as PsycArticles, CINAHL Complete, MEDLINE, and ERIC. The potential studies were assessed based on predetermined criteria for inclusion and disqualification. We included peer-reviewed publications that presented data on the experiences of nursing workers in various situations. research using any qualitative methodology were included, and the incorporated research were examined and evaluated utilizing a theme synthesis methodology. The examination of study quality was conducted utilizing the Critical Appraisal Skills Programme checklist specifically designed for qualitative research. Nine trials, including a total of 91 nurses, were included. Four primary themes were identified: the prevalence of polypharmacy among older persons, the significance of multidisciplinary teams, the role of nursing in caring for older adults, and the challenges associated with adopting polypharmacy management. Healthcare providers must be mindful of the effects of polypharmacy on the lives of older persons and recognize the significance of team-based polypharmacy care in providing assistance to older adults. Nurses have a crucial role in providing care for older persons who are taking several medications, a condition known as polypharmacy. As a result, it is important to empower nurses and include them in the administration of medicine. Keywords: nurse; elderly population; multiple medication use; theme synthesis